1989
DOI: 10.1017/s0003356100032451
|View full text |Cite
|
Sign up to set email alerts
|

Effects on performance and behaviour of mixing 20-kg pigs fed individually

Abstract: The effects of mixing on agonistic behaviour and performance were studied in 90 individually fed pigs, grouped at a mean live weight of 23 kg by one of the following three methods: (1) six unmixed littermates; (2) three pigs from each of two litters; and (3) one pig from each of six litters.Unmixed animals (treatment 1) did not fight and the mode of fighting differed between treatment 2 and 3. Mixing decreased daily weight gain in the period 23 to 100 kg for barrows, but not for gilts. For gilts, food conversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
40
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 6 publications
5
40
0
Order By: Relevance
“…Rushen (1987) observed that when pairs of pigs from two litters are combined, one pig from each litter is involved in the majority of all inter-litter encounters, and the social status of both littermates seems to be determined by the outcome of that aggression. Combining three pigs from each of two litters yields similar results (Rundgren and Lofquist 1989). An alternative to this hypothesis is that littermates have similar characteristics (strength, tenacity, etc.)…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Rushen (1987) observed that when pairs of pigs from two litters are combined, one pig from each litter is involved in the majority of all inter-litter encounters, and the social status of both littermates seems to be determined by the outcome of that aggression. Combining three pigs from each of two litters yields similar results (Rundgren and Lofquist 1989). An alternative to this hypothesis is that littermates have similar characteristics (strength, tenacity, etc.)…”
Section: Resultsmentioning
confidence: 79%
“…Social factors which have been studied include group size (Kornegay and Notter 1984;Gonyou et al 1992;Gonyou and Stricklin 1996), weight variation (Tindsley and Lean 1984;Gonyou et al 1986;Rushen 1987), variation in aggressiveness (Erhard et al 1996), and number of pigs per litter (Friend et al 1983;Blackshaw et al 1987;Rundgren and Lofquist 1989). Littermates fight little among themselves when moved to a different pen (Friend et al 1983;Rundgren and Lofquist 1989), or when co-mingled with pigs from other litters, but inter-litter agression is intense (Stookey et al 1986). Most studies on regrouping pigs combine equal numbers from each litter (Friend et al 1983;Blackshaw et al 1987;Rundgren and Lofquist 1989).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were reported by Hyun et al (1998) in a study with 35-kg pigs. In contrast, however, Rundgren and Lofquist (1989) showed that whereas regrouping reduced ADG by 2% and FCE by 3% from 23 to 100 kg, it had no effect on VFI. Similarly, regrouping 8-wk-old pigs did not have any long-term effect on performance, thus indicating that regrouping is a transient stressor that pigs can overcome if given sufficient time.…”
Section: Ii34 Regroupingmentioning
confidence: 69%
“…This aggression is associated with a reduction in the rate and efficiency of BW gain and poorer meat eating quality, carcass gradings, and maternal ability (Rundgren and Löfquist, 1989;Tan et al, 1991;Warriss et al, 1998;Løvendahl et al, 2005). It also increases the risk of infection, reduces immunocompetence, and increases the risk of disease spread (Morrow-Tesch et al, 1994).…”
Section: Introductionmentioning
confidence: 99%